2021
DOI: 10.3389/fphar.2021.750857
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress About Glioma Stem Cells in the Immune Microenvironment of Glioma

Abstract: Gliomas are the most common primary tumors of the central nervous system. Due to the existence of the blood-brain barrier and its unique regional immune characteristics, the study of the immune microenvironment of gliomas is particularly important. Glioma stem cells are an important cause of initiating glioma, promoting tumor progression and leading to tumor recurrence. Immunotherapeutic strategies targeting glioma stem cells have become the focus of current research. This paper will focus on the research prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Circulating neutrophils in the blood home to the hypoxic tumor microenvironment (TME), where they become heterogenous tumor-associated neutrophils (TANs), an essential component of immunosuppressive TME that contributes to cancer progression and therapeutic resistance 12,17 . Similar to macrophages, anti-tumor N1 and pro-tumor N2 phenotypes of TANs were found within the hypoxic TME [18][19][20][21] . Various therapeutic strategies have been developed to directly target neutrophils with a focus on neutrophil depletion or inhibition 12,22 , leading to several clinical trials (e.g., CCR5 inhibitor Maraviroc in NCT03274804).…”
mentioning
confidence: 74%
“…Circulating neutrophils in the blood home to the hypoxic tumor microenvironment (TME), where they become heterogenous tumor-associated neutrophils (TANs), an essential component of immunosuppressive TME that contributes to cancer progression and therapeutic resistance 12,17 . Similar to macrophages, anti-tumor N1 and pro-tumor N2 phenotypes of TANs were found within the hypoxic TME [18][19][20][21] . Various therapeutic strategies have been developed to directly target neutrophils with a focus on neutrophil depletion or inhibition 12,22 , leading to several clinical trials (e.g., CCR5 inhibitor Maraviroc in NCT03274804).…”
mentioning
confidence: 74%
“…Through geospatial analyses of human GBM tumors, MDSCs were found in close proximity to CD133 + and SOX2 + GSCs; these GSCs were found to secrete the cytokine macrophage migration inhibitory factor (MIF) to recruit MDSCs ( 218 ), as well as chemokine secretion of CCL2 and CCL5 ( 15 ). Gliomas also overexpress chemokine ligands 1 and 2 (CXCL1 and CXCL2, respectively), promoting the recruitment of MDSCs from the bone marrow towards the tumor ( 227 ). A study of breast cancer found that secretion of interleukin-6 (IL-6) by tumor cells can recruit and induce an immunosuppressive phenotype in MDSCs ( 131 ).…”
Section: Gsc-immune Cell Interactions In the Tmementioning
confidence: 99%
“…Adoptive cell therapy is a passive immunotherapy method in which a large number of amplified and activated immune cells after in vitro genetic engineering or screening activation are transfused back into the patient to enhance immune responses in the tumor microenvironment and directly or indirectly achieve tumor-killing effects (100). Unlike T cells and B cells, natural killer (NK) cells can express high levels of effector molecules with cytotoxicity, including perforin and granase B, making NK cells the most widely used in adoptive immunotherapy (100,101). However, the antitumor functions of NK cells in solid tumors are still unclear.…”
Section: Utmd-mediated Adoptive Cell Immunotherapymentioning
confidence: 99%